PERAN STAKEHOLDER DALAM PENGEMBANGAN PARIWISATA DI KAWASAN DATARAN TINGGI DIENG KABUPATEN BANJARNEGARA - Alvianita, Vivi; Subowo, Ari; Santoso, R. Slamet (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
Tourism development is one of the effective strategies to improve the welfare of local communities through optimizing the potential of the region. Dieng Plateau area is one of the priority tourist destinations in Banjarnegara Regency. This research aims to identify stakeholders involved in tourism development in the Dieng Plateau Area of Banjarnegara Regency and analyze the roles of these stakeholders. The methodology used is a qualitative approach with data collection through interviews, observations, and documentation. Stakeholders involved in tourism development include the Dieng Kulon Village community, Pokdarwis Dieng Pandawa, Dieng Kulon Village Government, Banjarnegara Regency Tourism and Culture Office, UPTD Dieng Tourism Area, Ministry of PUPR, Central Java Cultural Heritage Conservation Center (BPCB), Perhutani, Bank Indonesia, Bank BTN, PT Geodipa Energi, Universities and the media. The results of the study indicate that primary stakeholders consisting of local communities and Pokdarwis Dieng Pandawa act as coordinators, facilitators, implementers, and accelerators. Key stakeholders consisting of village government and local government act as policy creators, coordinators, facilitators, implementers, and accelerators, while secondary stakeholders consisting of government, community, companies, academics and media act as facilitators, implementers, and accelerators. However, the role of these stakeholders is said to be not optimal because there are still problems that arise and the implementation of the program is not optimal.